Literary Astronomy: teaching and dissemination in astronomy through Cordel Literature - Anjos, Zowguifer Emilio Nolasco dos; Alves, Gabriel Soroldoni; Ribeiro, Kaio Rodrigues; Bossan, Maria Cristina de Souza; Machado , Sofia de Souza (Cadernos de Astronomia, 2023)
Astronomy is a science that has been present in humanity since the beginning of time and its concepts and research are indispensable for the evolution of society. Despite its great importance, there are problems regarding the teaching and learning of this science in elementary schools, and new instruments and tools are needed to promote a better understanding and dissemination of this important science. Therefore, in this work, we will make a theoretical overview of the problems related to the teaching of astronomy, the use of string literature to teach this science, the use of social networks as a tool for the dissemination of knowledge and the creation of the Literary Astronomy Project: an Instagram page for the dissemination and teaching of the main concepts of astronomy using string literature and its successes during the time of operation.
Keywords: Astronomy; Teaching; Cordel; Social Networking